Necessary Conditions for Optimal Permissible Placement by the height of the Transitive Directed Tree with One Root (part second) - Khachaturyan, Armen (Mathematical Problems of Computer Science, 2021)
The present paper is the second part of the paper [1]. Here we have introduced a couple of additional concepts and have obtained some additional necessary conditions for the solution of the problem formulated in paper [1].